Quantifying comprehension gains after repeated listening by students of Spanish with different listening ability: an exploratory study. (2nd January 2017) - Rodrigo, Victoria
ABSTRACT: Repeated listening—listening to a passage several times for content and information—is considered an effective strategy to improve listening comprehension, but so far, no study has reported how much understanding increases with each repetition. This study is exploratory in nature and analyzes quantitatively how much 48 students with different degrees of listening ability understand after each repeated listening. The study shows that although the amount of total comprehension relates to learners' listening ability (low, medium, high), comprehension gains—new information understood after the first and second repetition—do not relate to learners' listening ability. The data indicate that understanding increased at a similar rate after the first repetition, 14% more, and after the second repetition, 9.3% more, in the three groups. These results suggest that there is benefit in repeated listening and propose its use as an independent learning tool that works at different levels of listening ability.